Dapagliflozin versus empagliflozin in patients with chronic kidney disease - Alnsasra, Hilmi; Tsaban, Gal; Solomon, Adam; Khalil, Fouad; Aboalhasan, Enis; Azab, Abed N.; Azuri, Joseph; Hammerman, Ariel; Arbel, Ronen (Frontiers in Pharmacology, 2023)
Background and Aim: Dapagliflozin and empagliflozin have demonstrated favorable clinical outcomes among patients with chronic kidney disease (CKD). However, their comparative monetary value for improving outcomes in CKD patients is unestablished. We examined the cost-per-outcome implications of utilizing dapagliflozin as compared to empagliflozin for prevention of renal and cardiovascular events in CKD patients. Methods: For calculation of preventable events we divided the allocated budget by the cost needed to treat (CNT) for preventing a single renal or cardiovascular event. CNT was derived by multiplying the annualized number needed to treat (aNNT) by the annual therapy cost. The aNNTs were determined based on data from the DAPA-CKD and EMPEROR-KIDNEY trials. The budget limit was defined based on the threshold recommended by the United States’ Institute for Clinical and Economic Review. Results: The aNNT was 42 both dapagliflozin (95% confidence interval [CI]: 34-59) and empagliflozin (CI: 33-66). The CNT estimates for the prevention of one primary event for dapagliflozin and empagliflozin were comparable at $201,911 (CI: $163,452-$283,636) and $209,664 (CI: $164,736-$329,472), respectively. However, diabetic patients had a higher CNT with dapagliflozin ($201,911 [CI: $153,837-$346,133]) than empagliflozin ($134,784 [CI: $109,824-$214,656]), whereas non-diabetic patients had lower CNT for dapagliflozin ($197,103 [CI: $149,029-$346,133]) than empagliflozin ($394,368 [CI: $219,648-$7,093,632]). The CNT for preventing CKD progression was higher for dapagliflozin ($427,858 [CI: $307,673-$855,717]) than empagliflozin ($224,640 [CI: $169,728-$344,448]). For preventing cardiovascular death (CVD), the CNT was lower for dapagliflozin ($1,634,515 [CI: $740,339-∞]) than empagliflozin ($2,990,208 [CI: $1,193,088-∞]). Conclusion: Among patients with CKD, empagliflozin provides a better monetary value for preventing the composite renal and cardiovascular events in diabetic patients while dapagliflozin has a better value for non-diabetic patients. Dapagliflozin provides a better monetary value for the prevention of CVD, whereas empagliflozin has a better value for the prevention of CKD progression.